SIGNIFIKANSI PENGEMBANGAN MUTU PENDIDIKAN ARAB SAUDI - Sirojudin, Didin; -, Waslah (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2020)
A country has different challenges and problems in improving the quality of its education. Education is one of the most important aspects for the sustainability of people's lives through the means of a country's quality level of education. It can be seen that the country's quality position compared to other countries education is often used as a benchmark for progress of a country Therefore every country is competing to advance the field of education in order to achieve this progress the conditions are carried out by various countries in the world including Islamic countries, Under the influence of modern culture, the system of primary, secondary, school- vocational schools, technical schools, and arrive at university systems in the Arab and Islamic world are updated and adjusted according to western patterns as well as syllabus and curriculum preparation. The adaptation that is meant here is not to mean swallowing everything from the West, but rather an advanced western education system and form adapted to the philosophy of Islamic Education. In the national development effort, the education system is burdened with 3 objectives namely to provide at least basic education for the entire population, to prepare students with the various skills needed for economic development that is constantly changing, to educate children in beliefs, practices , Islamic values.